Human-Centered Engineering: Integrating Human Factors in Modern Engineering System Design - Dwiyanto, Dwiyanto (Pt. Anagata Sembagi Education, 2026)
This study explores the integration of human factors into modern engineering systems through a human-centered engineering approach that emphasizes safety, usability, and long-term socio-technical sustainability. The increasing complexity of engineering systems, driven by digitalization and automation, necessitates a shift from technology-centered design toward approaches that prioritize human interaction and well-being. The study employs a mixed-method approach, combining a systematic literature review, expert interviews, and case study analysis across industrial, healthcare, and digital system contexts. Data were analyzed using thematic analysis, content analysis, and comparative evaluation to identify key dimensions of human-centered engineering, including physical, cognitive, and organizational ergonomics, as well as Human-Centered Design (HCD) and Human Systems Integration (HSI). The results indicate that integrating human-centered components significantly enhances system performance, particularly in terms of safety, usability, efficiency, and adaptability. The discussion reveals that the synergy between human factors and digital technologies, such as human modeling and simulation, plays a critical role in optimizing system design. However, challenges remain in terms of late integration, interdisciplinary collaboration, and limited representation of human factors in digital engineering frameworks. In conclusion, the development of modern engineering systems requires a comprehensive human-centered strategy that aligns technological innovation with human needs to achieve resilient, efficient, and sustainable systems.